PROBLEMS OF STUDYING THE VOCABULARY OF THE RUSSIAN LANGUAGE IN NATIONAL GROUPS - Raimjanova Makhbuba Nomanovna (Journals Park Publishing, 2025)
The study of the Russian language poses unique challenges for individuals from national groups due to the linguistic differences and complexities involved. This article explores the specific problems encountered by national groups when studying the vocabulary of the Russian language, including issues related to phonetics, grammar, semantics, and cultural nuances. Strategies to address these challenges and enhance vocabulary acquisition among individuals from diverse linguistic backgrounds are also discussed.
Keywords: Russian Language, Vocabulary Acquisition, National Groups, Linguistic Differences, Cultural Nuances.